A realist review of interventions to dismantle mental health and substance use related structural stigma in healthcare settings - Javeed Sukhera; Stephanie Knaak (Elsevier, 2022)
Efforts to address mental illness stigma within the healthcare sector have not produced sufficient or sustained changes to delivery, quality, or models of care. One such reason is that many anti-stigma efforts tend to be targeted at interpersonal aspects of stigma, seeking to reduce prejudicial attitudes and improve discriminatory behaviors. Shifting attention to structural aspects of stigma may have unique potential to advance stigma reduction into the future. In this study, the authors conducted a realist case study of interventions to address structural stigma in healthcare organizations. Utilizing a realist multiple explanatory case study approach, authors reviewed data from 62 cases. After developing their initial program theory, 6 exemplar cases were analyzed for possible context-mechanism-outcome configurations. Results suggest that effective interventions required organizational readiness to disrupt existing power asymmetries, shared governance infrastructures, and an alignment of values despite historical mistrust between disparate partners. Mechanisms for change involved proactive management of resistance, disruptive innovation, co-designing processes, and embedding structural change into existing policy. Outcomes included sustainability, reduced coercion, and improved trust. Findings suggest that interventions to address structural stigma can produce sustained policy and practice change if organizations embrace power sharing and trust building while embedding change within policies and governance structures.